Air Pollution and the Risk of Cardiac Defects: A Population-Based Case-Control Study. Issue 44 (November 2015) - Hwang, Bing-Fang; Lee, Yungling Leo; Jaakkola, Jouni J.K.
Abstract : Abstract: Previous epidemiologic studies have assessed the role of the exposure to ambient air pollution in the development of cardiac birth defects, but they have provided somewhat inconsistent results. To assess the associations between exposure to ambient air pollutants and the risk of cardiac defects, a population-based case-control study was conducted using 1087 cases of cardiac defects and a random sample of 10, 870 controls from 1, 533, 748 Taiwanese newborns in 2001 to 2007. Logistic regression was performed to calculate odds ratios for 10 ppb increases in O3 and 10 μg/m 3 increases in PM10 . In addition, we compared the risk of cardiac defects in 4 categories-high exposure (>75th percentile); medium exposure (75th to 50th percentile); low exposure (<50th–25th percentile); reference (<25th percentile) based on the distribution of each pollutant. The risks of ventricular septal defects (VSD), atrial septal defects (ASD), and patent ductus arteriosus (PDA) were associated with 10 ppb increases in O3 exposure during the first 3 gestational months among term and preterm babies. In comparison between high PM10 exposure and reference category, there were statistically significant elevations in the effect estimates of ASD for all and terms births. In addition, there was a negative or weak association between SO2, NO2, CO, and cardiac defects. The study proved that exposure to outdoor air O3 and PM10 during the first trimester of gestation may increase the risk of VSD, ASD, and PDA.